SAINS DAN DUNIA MANUSIA - L. Bambang Sugiharto (Studia Philosophica et Theologica, 2004)
In spite of its useful and significant results, science has become also a threat to the human world in some respects. One of the underlying factors leading to the negative outcome is the epistemological framework of positivism. The most decisive critique of such epistemology comes from Phenomenology. It is found out that the primary and most basic reality is our pre-reflective world the amorphous and multi-dimensional flux which precedes the “objective” world of science. Crusequently the particular mode of articulation of this basic human reality is not actually science, but rather, philosophy, religion and art. If the scientific world is to make a significant contribution to the evolution of human civilization, it must intensify its creative relationship with the three domains